2001
DOI: 10.21236/ada593334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Army/Air Force and Private-Sector Physicians' Total Compensation, by Medical Specialty (Supplement to Health Professions' Retention-Accession Incentives Study)

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The first phase was a comparative analysis of compensation between uniformed and private-sector health care professionals at logical military career junctures [2,3,4]. This analysis was an essential first step because we needed to understand whether a militarycivilian pay gaps exists, how large it is, and at what career junctures to evaluate the effect of pay on retention during the second phase of this study.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The first phase was a comparative analysis of compensation between uniformed and private-sector health care professionals at logical military career junctures [2,3,4]. This analysis was an essential first step because we needed to understand whether a militarycivilian pay gaps exists, how large it is, and at what career junctures to evaluate the effect of pay on retention during the second phase of this study.…”
Section: Approachmentioning
confidence: 99%
“…To answer this question, we first conducted a comparative analysis of compensation of 24 uniformed and private-sector salaried physician specialties at logical military career junctures [2,3,4]. We found that a uniformed-civilian pay gap exists at every career juncture for all specialties considered.…”
Section: Physicians Introductionmentioning
confidence: 99%